Use of Intraoperative Technology to Perform a Cam Resection During Hip Arthroscopy for Femoroacetabular Impingement Syndrome - Sachin Allahabadi MD; Thomas W. Fenn BS; Reagan Chapman BS; Shane J. Nho MD, MS (SAGE Publishing, 2023)
Background: The learning curve for the surgical treatment of cam deformities in femoroacetabular impingement syndrome (FAIS) presents a challenge for young or inexperienced surgeons, with the leading cause of failed hip arthroscopy being incomplete resection. Historically, alpha angle measurements are typically used perioperatively to both diagnose cam deformity and evaluate the adequacy of cam resection. The computer-assisted Styker HipCheck system offers the surgeon real-time alpha angle measurements, assisting with the execution of cam resection. Indications: The indication for use is any hip arthroscopic procedure for femoroacetabular impingement requiring osteochondroplasty of cam deformity. Advantages of the HipCheck system include shortened operative time; reduced risk of inadequate or over-resection; accelerated learning curve; no requirement of preoperative computed tomographic imaging or pre-planning; being noninvasive, portable, and not requiring additional instruments; increased patient and surgeon satisfaction; and allowance of repeated quantitative and visual assessment, which is particularly beneficial for more difficult regions, such as posteromedial and posterolateral, to view the femoral head/neck. Technique Description: Briefly, after intra-articular procedures are complete, the peripheral compartment is accessed. We prefer a T-type capsulotomy. Next, the cam deformity is registered on Stryker HipCheck software, automatically calculating alpha angles as the hip is dynamically moved through 6 registered positions. A standard cam resection is then performed. Once complete, the hip is dynamically assessed and again registered with the HipCheck system in the same 6 positions to ensure adequate resection has been performed. Results: When comparing patients with FAIS undergoing computer-guided resection or standard resection, both surgical interventions demonstrated successful reduction in alpha angle and no difference in degree of resection. In addition, the various computer-guided views exhibited good correlations to clinical radiographs. Discussion: The HipCheck intraoperative system allows the surgeon to evaluate the adequacy of cam resection through the use of automated alpha angles. Furthermore, the system offers instantaneous feedback of cam resection at any desired position of the hip. This intraoperative technology may offer less experienced surgeons an aid when performing hip arthroscopy for cam resection in the setting of femoroacetabular impingement. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.